The influence of synthetic polyhydroxybutyrate on selected properties of novel polyurethanes for medical applications. Part I. Polyurethanes with aromatic diisocyanates in hard segments - Brzeska, J.; Dacko, P.; Janeczek, H.; Kowalczuk, M.; Janik, H.; Rutkowska, M. (Polimery, 2021)
Polyurethanes (PUR) containing 37% of soft segments, obtained by prepolymer chain extension in the reaction of diphenylmethane 4,4’-diisocyanate (MDI) with 1,4-butanediol (1,4-BD) were synthesized. Soft segments of PUR were built either of poly([R,S]-3-hydroxybutyrate) (a-PHB) and polycaprolactonediol (PCL) or a-PHB and polyoxytetramethylenediol (PTMG) (Table 1). The effects of a presence of synthetic a-PHB in the PUR chain on the thermal and mechanical properties, water and vegetable oil sorption, and sterilization efficiency of the materials prepared, designed to medical applications, were investigated. It was shown by DSC method that the introduction of a-PHB with methyl side group to the soft segment disturbed phase segmentation leading to glass transition temperature (Tg) shift to higher values (Tables 2, 3). The presence of a-PHB in the chain increases the hydrophilicity of the products, causing better water absorption and lower absorption of vegetable oil (Table 4, Fig. 1). The results of microbiological tests and the mechanical properties of a-PHB containing PUR samples show that such materials can be subjected to plasma sterilization without surface flaw (Table 5) and PUR obtained can be used for medical applications if not high mechanical strength is required.